Oenococcus oeni Lifestyle Modulates Wine Volatilome and Malolactic Fermentation Outcome - Tofalo, Rosanna; Battistelli, Noemi; Perpetuini, Giorgia; Valbonetti, Luca; Rossetti, Alessio Pio; Perla, Carlo; Zulli, Camillo; Arfelli, Giuseppe (Frontiers in Microbiology, 2021)
In this study 9 Oenococcus oeni strains were tested for their ability to adhere to polystyrene using mMRS and wine as culture media. Moreover, planktonic and biofilm detached cells were investigated for their influence on malic acid degradation kinetics and aroma compounds production. Three strains were able to adhere on polystyrene plates in a strain dependent way. In particular, MALOBACT-T1 and ISO359 strains mainly grew as planktonic cells, while ISO360 the sessile one. The strain dependent adhesion ability was confirmed by Confocal Laser Scanning Microscopy. Planktonic and biofilm detached cells showed a different metabolism. In fact, biofilm detached cells had a better malic acid degradation kinetic and influenced the aroma composition of resulting wines, acting on the final concentration of ester, higher alcohols, and organic acids. Oenococcus oeni in biofilm lifestyle seems to be a suitable tool to improve malolactic fermentation and to contribute to wine aroma. The industrial scale application of this strategy should be implemented to develop novel wine styles.